2016
DOI: 10.1038/srep34081
|View full text |Cite
|
Sign up to set email alerts
|

Expression profiling of cutaneous squamous cell carcinoma with perineural invasion implicates the p53 pathway in the process

Abstract: Squamous cell carcinoma (SCC) is the second most common cancer worldwide and accounts for approximately 30% of all keratinocyte cancers. The vast majority of cutaneous SCCs of the head and neck (cSCCHN) are readily curable with surgery and/or radiotherapy unless high-risk features are present. Perineural invasion (PNI) is recognized as one of these high-risk features. The molecular changes during clinical PNI in cSCCHN have not been previously investigated. In this study, we assessed the global gene expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 34 publications
1
36
1
Order By: Relevance
“…(142) This study identified a wide range of genes that were differentially up or downregulated across the groups. Several statistically and biologically significant differentials were identified, including downregulation of transglutaminase 3 (TGM3) and up-regulation of lysyl oxidase like 2 (LOXL2) and EphA3 in the perineural spread cohort (Figure 11).…”
Section: Genetic Profile Of Cscchn With and Without Pnsmentioning
confidence: 97%
See 4 more Smart Citations
“…(142) This study identified a wide range of genes that were differentially up or downregulated across the groups. Several statistically and biologically significant differentials were identified, including downregulation of transglutaminase 3 (TGM3) and up-regulation of lysyl oxidase like 2 (LOXL2) and EphA3 in the perineural spread cohort (Figure 11).…”
Section: Genetic Profile Of Cscchn With and Without Pnsmentioning
confidence: 97%
“…TGM3 and LOXL2 were selected for further study in the subcutaneous mouse model, however due to small numbers and variable tumour growth no significant conclusions could be drawn. (51,142) Generous provision of the raw microarray data allowed differential expression levels of Eph receptors and ephrin ligands to be specifically reviewed as part of this thesis (Table 5). In addition to up-regulation of EphA3, EphA4 and EphA5 were elevated without reaching statistical significance.…”
Section: Genetic Profile Of Cscchn With and Without Pnsmentioning
confidence: 99%
See 3 more Smart Citations